(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
When discussing transitions of deaf and hard of hearing adolescents, we have to perceive them holistically, and to recognize the nature and complexity of the relationships between traditional transitions. Measures of ‘successful’ or ‘unsuccessful’ transitions, do not necessarily align with the traditional events-based and institutional transitions. We need to broaden our understandings of transitionary processes and desirable outcomes. Successful transition begins with trusting deaf and hard of hearing students to lead their own transition planning. Autonomy of deaf adolescents is linked to better employment with more opportunities for advancement and higher income. Autonomous beliefs, capacities, and actions are associated with improved outcomes for students with disabilities. When we are discussing employment opportunities, it is evident that there has been a shift of the traditional parameters of the industrial society. The old traditional occupations are replaced by the necessity for individuals to adapt to new standards of work and changing labour market conditions, by for example, re-training or switching occupations. To support development of autonomy, environments must facilitate opportunities for the individual to take control over their own lives, to make choices and decisions freely. When we discuss independence and autonomy, we must also relate it to new and uprising technologies. Technology can mean increased access, independence, and reliance of oneself. With high expectations from parents and teachers and using technology for meaningful education, these deaf and hard of hearing adolescents will be ready for college and careers.